Performance Degradation Analysis of WLAN-Based Train-to-Ground Communication in Jakarta LRT - ABRAHAM DHAYAN JONATHAN; ERNA SRI SUGESTI; BUDI PRASETYA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Operational disruptions on the Jakarta Light Rail Transit (LRT) during 2023–2025 indicate issues related to the signal loss between the train's communication system and surface radio devices. This research investigates the causes of signal loss through field testing, simulations, and theoretical analysis. Field testing showed a measured Received Signal Level (RSL) of approximately −79 dBm, while simulation results with Atoll and theoretical approaches ranged from −70 to −65 dBm and −50.62 to −66.18 dBm. Coverage analysis based on Atoll simulation revealed signal-free areas between adjacent Wireless Radio Units (WRUs), leading to a loss of connectivity for 1.12 second. The SINR values obtained, ranging from 2 to 8 dB, resulted in a BER of up to 10⁻² and a PER of 100%, as simulated using MATLAB. Doppler analysis confirms slow fading conditions, showing that the train's mobility factor has no effect.